Interactions between Bromus tectorum, grasshoppers, and native plants in sagebrush steppe communities - Cumberland, Catherine, author; Paschke, Mark, advisor; Cooper, David, committee member; Jonas, Jayne, committee member; Pejchar, Liba, committee member (Colorado State University. Libraries, 2014)
Invasion by the exotic grass Bromus tectorum L. (cheatgrass) has produced widespread, persistent changes in the Intermountain West. As a result of this and other disturbances, sagebrush shrubland is among North America's most imperiled ecosystems. Restoration of B. tectorum-infested areas has often been unsuccessful, and there is a need to understand the factors limiting revegetation success. There is evidence that B. tectorum is a superior competitor for space and resources. But it's also possible that B. tectorum dominance is enhanced by native herbivores through the mechanism of apparent competition: species competing indirectly through shared natural enemies. If an invasive exotic is a less preferred food source for herbivores than native plants, per capita feeding impacts may increase on natives, thus facilitating exotic proliferation. In sagebrush shrubland, grasshoppers are often the dominant herbivores. Their feeding patterns have been shown to limit and structure plant distributions. The objective of this study was to elucidate whether grasshoppers may be promoting B. tectorum spread through herbivore-mediated apparent competition. Using native plants commonly seeded in sagebrush restoration projects and the native generalist grasshopper Melanoplus bivittatus in laboratory trials and greenhouse experiments, I tested how grasshopper herbivory affects native plants in comparison to B. tectorum. Grasshoppers significantly increased mortality rates for most native plants but had minimal impact on B. tectorum mortality. Certain native species were much more highly preferred and / or impacted by herbivory, including the keystone shrub Artemisia tridentata (big sagebrush). However, several native species were either less preferred or more tolerant of herbivory than B. tectorum, and could therefore be good restoration candidates where grasshoppers are common. In addition, my results suggest B. tectorum could promote population increase in certain grasshopper species, particularly agricultural and rangeland pests. Study results could provide guidance regarding seed mixes and possible control of insect herbivores to improve restoration success in B. tectorum-invaded areas.
Keywords: grasshopper; Melanoplus bivittatus; plant-insect interactions; cheatgrass; Bromus tectorum